HYGIENIC FOUNDATIONS OF TUBERCULOSIS PREVENTION - Xusnidin Odilovich, Xojimatov (The latest news and research in education, 2024)
There are significant hygienic measures and the importance of developing proper hygiene culture in preventing tuberculosis. To reduce the spread of the disease and prevent its occurrence, a comprehensive set of actions is required, including not only individual hygiene practices but also public hygiene, strengthening sanitation measures, environmental cleaning, and providing information to the population. Special attention should be given to personal hygiene.